Глобальні дисбаланси в контексті світової фінансової кризи - Александрова, М.О. (Культура народов Причерноморья, 2013)
З початку 1990-х років глобальні дисбаланси стали предметом наукових теоретичних обговорень, проте криза 2007-2009 років змінила ситуацію, зробивши їх темою дискусій на рівні світової економічної та політичної спільноти. У статті подано різні підходи до визначення поняття „глобальні дисбаланси” та різні погляди на їх роль у розгортанні останньої фінансової кризи – як частини кризи, її причини та думки про те, що глобальні дисбаланси – це міф. С начала 1990-х годов дисбалансы стали предметом научных теоретических обсуждений, но кризис 2007-2009 годов изменил ситуацию, сделав их темой дискуссий на уровне мировой экономической и политической общественности. В статье представлены разные подходы к определению понятия „глобальные дисбалансы” и разные взгляды на их роль в последнем финансовом кризисе – как части кризиса, причины возникновения кризиса, а также тезиса о том, что глобальные дисбалансы – это миф. Since the beginning of the 1990th the global imbalances became the problem of theoretical discussions. The global crisis 2007-2009 put global imbalances to a center of the international economic policy debates. This article summarizes the different approaches to the definition of the „global imbalances” and their role in the last financial crises – imbalances as the part of crisis, imbalances as the cause of crisis and a viewpoint that imbalances are the „myth”. Nowadays the global imbalances are one of the most complex macroeconomic problem that should be solved by economists and policy makers. On the G-20 level were implemented the number of indicators to estimate imbalances. These indicators correspond with the main sides of imbalances – difference in interest rates, budget deficits, national debts, private savings and debts, current account positions and trade imbalances.